2020
DOI: 10.1182/blood-2020-136554
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell Acute Lymphoblastic Leukemia Can be Subdivided into Six Genetically Distinct Subtypes with Prognostic Impact By Combination of Whole Genome and Whole Transcriptome Data

Abstract: Background: T-cell acute lymphoblastic leukemia (T-ALL) is a rare aggressive neoplasm accounting for ∼20% of all ALL cases. It is more common in adults than in children, although the incidence decreases with older age. Subclassification of T-ALL cases according to WHO is so far solely based on the immunophenotype. Although a number of common molecular aberrations have been described in T-ALL, a molecular classification of T-ALLs so far is missing. Aim: (1) Molecular subclassification of T-ALL ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In addition, gene mutations and signaling pathway alterations based on genomic analyses are important predictors of clinical outcome in adult ALL ( 16 ). Up-to-date risk stratification of T-ALL patients based on the genome analyses showed that gene mutations had impacts on prognosis and were conducive to subdivide cases into different risk groups ( 17 ). Therefore, integration of gene mutations into current risk stratification criteria may be beneficial to improve prognosis identification and therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, gene mutations and signaling pathway alterations based on genomic analyses are important predictors of clinical outcome in adult ALL ( 16 ). Up-to-date risk stratification of T-ALL patients based on the genome analyses showed that gene mutations had impacts on prognosis and were conducive to subdivide cases into different risk groups ( 17 ). Therefore, integration of gene mutations into current risk stratification criteria may be beneficial to improve prognosis identification and therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%